Building Tests For Some Fundamental Skills (Forehand and backhand shots and service) In Lawn Tennis - Star, Hasnaa (Journal of Physical Education, 2019)
Lawn tennis is one of the sports that require level specification to establish a scientific base for tests and training. The importance of tests and measurements are shown through diagnoses, classification, motivation, selection and anticipation. This means that tests and measurements are results of continuous scientific development. The aim of the research was to build skill tests to measure some fundamental skill in lawn tennis. The subjects of the research were 75 individuals. Tennis skill tests were applied on them, and then the results were treated using statistical methods. The researcher concluded standardizing tests through application of correct scientific bases.